DEVELOPMENT OF THE RENDANG INDUSTRIAL INNOVATION SYSTEM IN PAYAKUMBUH CITY - Imelfina Musthafa; Firwan Tan (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This research aims to examine efforts to develop an innovation system for the rendang industry in Payakumbuh City. The methodology used in this research is interviews with related parties regarding efforts to develop an innovation system for the rendang industry in Payakumbuh City. The results obtained are that there are various efforts to develop an innovation system for the rendang industry in Payakumbuh City, namely: the establishment of a rendang industrial center, rebranding of Payakumbuh City, the establishment of UPTD P3R, the establishment of the "IKOSERO" cooperative, the establishment of the School of Randang,collaboration and partnerships, technology implementation, marketing, HR training and development, as well as licensing and standardization. Government policy to provide support to the rendang industry in Payakumbuh is very necessary so that rendang in Payakumbuh City is able to have competitiveness in the national market and Payakumbuh rendang can enter the international market and become a food that is in demand by people throughout the world.